The role of financial literacy in moderating the effect of self-control and hedonic lifestyle on students’ financial decision-making - Ahmad Yudhira; Uswatun Hasanah (Insight Management Journal, 2026)
This study examines the effect of self-control and hedonic lifestyle on students’ financial decision-making, with financial literacy as a moderating variable. Using a quantitative approach, data were collected from 122 students and analyzed through moderation analysis using Andrew F. Hayes’s PROCESS Macro Model 1. The findings indicate that self-control does not have a significant direct effect on financial decision-making. However, when moderated by financial literacy, self-control shows a significant positive effect, suggesting that students with higher financial literacy are better able to translate self-control into sound financial decisions. In contrast, hedonic lifestyle has a significant negative effect on financial decision-making, while financial literacy does not significantly moderate this relationship. These results imply that financial literacy strengthens the positive role of self-control but may not be sufficient to reduce the adverse influence of a strong hedonic lifestyle. Practically, the study highlights the importance of integrating financial literacy education with behavioral strategies, such as budgeting practices, spending limits, and delayed purchasing decisions. Future studies are recommended to use longitudinal or experimental designs, involve larger and more diverse samples, and examine additional variables such as financial stress, impulsive buying, budgeting adherence, and exposure to buy-now-pay-later services.